Examining the Basic Level Teachers’ Perspectives and Practices on ELT Curriculum - Baskota, Prateet; Thapa, Punam (KMC Journal, 2023)
This study sought to answer how basic level English teachers define ‘curriculum’ and use it to investigate teachers’ perspectives on the curriculum. The purpose of this study is to investigate the beliefs and methods used by basic level English language teachers in Nepal concerning the basic level English curriculum. A qualitative method was employed. This study presents the participants’ perspectives on the basic level English curriculum and how it is really taught in classrooms. Additionally, the qualitative approach to data collecting and interpretation was used to obtain individual perspectives on how people would view and perceive the curriculum as a whole. In order to examine the experiences of the research participants, we used meaning-oriented procedures using semi-structured interviews. The study’s findings showed that even though the teachers are aware of the curriculum and its significance, they are unable to put it into practice in their actual classroom settings. We can infer from the participant data that although our participants have some theoretical knowledge of the curriculum, they are unable to apply it to their real-world circumstances.